Interreligious Citizenship Dalam Tafsir Qur'an Surah Al-Mumtahanah Ayat 8: Rekonstruksi Relasi Muslim dan Non-Muslim Pada Masyarakat Multikeyakinan - Zulfikar Fikar; Azifah Nurullah; Nur Alifah Muyasaroh; Athaya Zahra Nayna Ramadhani; Bilqis Nidaul Khair Daulay (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2026)
Contemporary citizenship discourse emphasizes the equal status of all citizens regardless of religious affiliation, ethnicity, or other social identities. Nevertheless, relations between Muslims and non-Muslims are often shaped by exclusive religious interpretations that may restrict social interaction and civic engagement across faith communities. This article examines Qur'an 60:8 (QS. Al-Mumtahanah) as a normative foundation for developing the concept of interreligious citizenship in multi-faith societies. Positioned within ongoing debates on Islam and citizenship, the study moves beyond the conventional framework of tolerance by proposing a more inclusive and participatory understanding of civic relations. This research employs a qualitative library-based approach using thematic Qur'anic interpretation, discourse analysis, and contextual hermeneutics. The primary data consist of Qur'an 60:8 and selected classical and contemporary Qur'anic commentaries analyzed comparatively. The findings reveal four key principles embedded in the verse that support the construction of interreligious citizenship: recognition of religious diversity, equality of civic status, justice in social relations, and shared civic participation. These principles indicate that the Qur'an not only promotes peaceful coexistence but also provides an ethical basis for inclusive citizenship across religious boundaries. The study contributes to the integration of Qur'anic interpretation and contemporary citizenship studies, offering a normative framework for fostering social cohesion and harmonious coexistence in plural societies.